PROBLEM PERLINDUNGAN HUKUM TERHADAP PERKAWINAN BEDA AGAMA DI INDONESIA: STUDI UU NO 1 TAHUN 1974 SERTA UU NO 39 TAHUN 1999 DAN HUKUM ISLAM - Cindy Silvy Foresty (Program Studi Hukum Keluarga Islam, 2016)
This research presents the relations among the Marriage Law, the Law on Human Rights and Islamic Law on interreligious marriage. Marriage Law was born in Indonesian contexs of the importance of family. Meanwhile the Law on Human Rights was enacted in themidst of law reformation to guarantee the rights of civilians and equity before the law. This article applies legal system theory as an alternative solution for interreligious marriage.